Slope Stability Analysis of the Bener Dam Cofferdam Using PLAXIS Application for Main Dam Construction Safety - Ferdiansyah Imran Halim; Sri Prabandiyani R Wardani; Kresno Wikan Sadono (Diponegoro University, 2025)
Slope stability is one of the methods used to determine the safety factor of a hydraulic structure, such as a cofferdam. A cofferdam functions to retain water and divert it into a diversion channel, which may be in the form of a conduit or tunnel. Assessing the safety factor of a cofferdam is crucial to ensuring the smooth progress of dam body embankment work. While many studies have been conducted on dam body slope stability, research on cofferdam slope stability remains limited. This study aims to analyze the slope stability of the Bener Dam cofferdam using the finite element method with the PLAXIS application to ensure that the main dam construction remains unaffected. The data used for slope stability analysis were obtained from the Final Report of Bener Dam and several literature sources. The slope stability modeling was evaluated under three conditions: after construction (empty water level), flood water level, and rapid drawdown. The results indicate that the safety factor values for all three conditions exceed the required threshold, with values of 1.369 for after construction, 1.824 for normal water level, and 1.215 for flood water level. These results confirm that the main dam construction is not affected by the stability of the cofferdam.